Socoflata gen. nov., described for two new planthopper species from the mountains in Socotra island (Hemiptera: Fulgoromorpha: Flatidae) - Stroiński, Adam; Malenovský, Igor; Świerczewski, Dariusz (Zootaxa, 2018)
A new genus of flatid planthoppers (Hemiptera: Fulgoromorpha: Flatidae) is described from the island of Socotra (Yemen): Socoflata gen. nov., for S. aurolineata sp. nov. and S. histrionica sp. nov. (type species). Habitus, male and female external and internal genital structures of the new species are illustrated and diagnosed. Both Socoflata species are abundant and syntopic in the evergreen montane woodland and dwarf shrubland at high elevations in the Hagher mountains in central Socotra and are likely endemics of this area.